Odpowiedzi

Najlepsza Odpowiedź!
2010-01-22T16:18:31+01:00
A)
[2x-y+3=3x-2y+11
[-2x-3y+10=x+y-7

2x-y-3x+2y=11-3
-2x-3y-x-y=-7-10

-x+y=8
-3x-4y=-17

y=8+x
-3x-4(8+x)=-17

y=8+x
-3x-32-4x=-17

y=8+x
-3x-4x=-17+32

y=8+x
-7x=15 /:(-7)

y=8+x
x=-15/7

y=8+(-15/7)
x=-15/7

y=8-15/7
x=-15/7

y=5 6/7
x=-15/7

b)
[x+2y-5=4y-x-3
[-3x+8y+5=x-6y+4

x+2y-4y+x=-3+5
-3x+8y-x+6y=4-5

2x-2y=2 /*2
-4x+14y=-1

4x-4y=4
-4x+14y=-1

10y=3 /:10
y=0,3

-4x+14y=-1
y=0,3

-4x+14*0,3=-1
y=0,3

-4x+4,2=-1
y=0,3

-4x=-1-4,2
y=0,3

-4x=-5,2 /:(-4)
y=0,3

x=1,3
y=0,3

c)
[-2x+3y+6=x+2y-6
[5x+8y-19=2x-3y-7

-2x+3y-x-2y=-6-6
5x+8y-2x+3y=-7+19

-3x+y=-12
3x+11y=12

12y=0 /:12
y=0

3x+11y=12
y=0

3x+11*0=12
y=0

3x+0=12
y=0

3x=12 /:3
y=0

x=4
y=0

d)
[x-2y+3=3x-3y+5
[6x+5y+1=y-2x

x-2y-3x+3y=5-3
6x+5y-y+2x=-1

-2x-5y=2 /*4
8x+4y=-1

-8x-20y=8
8x+4y=-1

-16y=7 /:(-16)
y=-7/16

8x+4y=-1
y=-7/16

8x+4*(-7/16)=-1
y=-7/16

8x-28/16=-1
y=-7/16

8x-1,75=-1
y=-7/16

8x=-1+1,75
y=-7/16

8x=0,75 /*100
y=-7/16

800x=75 /:800
y= -7/16

x=75/800
y=-7/16

x=3/32
y=-7/16










1 1 1
2010-01-22T16:25:19+01:00
A)
[2x-y-3x+2y=11-3
[-2x-3y-x-y=-7-10
[-x-y=7/*(-3)
[-3x-4y=-17
[3x+3y=-21
+
[-3x-4y=-17
-----------------
-y=-38/(-1)
y=38
1 2 1